2021
DOI: 10.1088/1757-899x/1036/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Cement Kiln Dust-Periwinkle Shell Ash Blends on Plasticity Properties of Two Selected Tropical Soils for use as Sustainable Construction Materials

Abstract: This paper investigated the effect of cement kiln dust (CKD) and periwinkle shell ash (PSA) on the plasticity characteristics of two lateritic soil. Two Soils (termed soil A and B) were collected from two selected locations within Osun State, Nigeria. Air-dried soil was treated with CKD and PSA blend in order of 0, 5, 10, 15, and 20% for CKD and 0, 2, 4, 6, 8 and 10% for PSA by dry weight of soil. The specific gravity of both soils increased with increase in CKD and PSA fillings. The Index properties such as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Hence the significant decrease in liquid and plastic limit values. Similar findings have been documented [19,21,22].…”
Section: Atterberg Limit Characteristi-cssupporting
confidence: 90%
“…Hence the significant decrease in liquid and plastic limit values. Similar findings have been documented [19,21,22].…”
Section: Atterberg Limit Characteristi-cssupporting
confidence: 90%
“…The study concluded that the composite sample achieved the optimum engineering properties at 15% CKD and 15% FA. An investigation of the effect of using CKD and periwinkle shell ash (PSA) blends on the plasticity of lateritic soil was carried out by Ekpo et al (2021) [49]. CKD at 0, 5, 10, 15, and 20% was used for soil treatment.…”
Section: Soil Stabilizationmentioning
confidence: 99%
“…It is important to note that the amendment of soil with non-conventional ameliorants which are sustainable and economical, has proved to be very successful due to their ability to perform anticipated outcomes in the geotechnical parameters of soft clay soil compared to conventional ameliorants. Thus, the emerging advances in construction materials have proved that diverse ameliorants rich in alumina and silica such as sawdust ash—quarry dust 5 , cement kiln dust—rice husk ash 6 , cement kiln dust—metakaolin 7 , 8 , cement kiln dust 9 , periwinkle shell ash 10 , oyster shell ash 11 , 12 , quarry dust 13 , marble dust—rice husk ash 14 , coconut husk ash 15 , corncob ash 16 , locust bean waste ash 17 , 18 , groundnut shell ash 19 – 21 , lime-rice husk ash 22 , bambara nut shell ash 23 , yam peel ash 24 , metakaolin 25 , mine tailings 26 , palm bunch ash 27 , cement kiln dust-periwinkle shell ash 28 , 29 , cow bone ash—waste glass powder 30 , sawdust ash—lime 31 , rice husk ash—sisal fibre 32 , coffee husk ash 33 , construction waste 34 , sawdust 35 , nanosilica 36 , electric arc furnace dust 37 , iron ore tailing 38 and so on have been utilised in the amendment studies of deficient soils and concrete structures. Conclusively, as a result of the positive outcomes recorded by the incorporation of solid wastes in soil amelioration studies, a comprehensive review was carried out on the trends in expansive soil stabilization using calcium-based stabilizer materials 39 .…”
Section: Introductionmentioning
confidence: 99%